Exercise in the heat: A double threat to the immune system? - Shephard, R. J. (The Physician and Sportsmedicine, 2001)
Review article of following items: - Manipulation of Body Temperatures During Exercise - Inhibition of Beta-Endorphins - Correlations With Stress Hormones - Expression of Adhesion Molecules and Cell Trafficking - Directions for Further Research